Sociology in America - Morgan, J (1966)
﻿ This thesis attempts to provide a comprehensive review of the teaching of sociology in universities and colleges in the United states in tne nineteenth century. (The primary sources are the catalogues and various other publications, such as presidential reports and alumni yearbooks, of 663 institutions from their foundings until the end of the academic year 1900-01). Evidence of the teaching of courses in sociology, or in some closely related study such as social science or social problems, was found in 227 of the total number of institutions. After some introductory observations on the extensive inclusion of sociology in American university curricula, the first chapter goes on to describe the nature of the sources used and to comment upon previous studies of a similar type, none of which have provided the sort of complete historical documentation of the rise of sociology teaching as the present study sets out to do. This specific development is set in the general context of higher education in the nineteenth century which saw a decline of older methods based upon the recitation system in favour of a more liberal attitude to teaching and research. The Land Grant College Act of 1862, with its particular encouragement of scientific training, and the influence of German ideals in higher education are singled out as movements of great importance for the changing conception of higher education. The second chapter contains a discussion of some of the first attempts at sociological writing in the United States, mostly before the Civil War. The largely Aristotelian and conservative views of the southern writers are contrasted with those of the Utopian social thinkers of the North. Here, as throughout the thesis, emphasis is placed upon the relationship between the attempts at sociological theory and the social context in which they arose. Chapter III describes in some detail the beginnings of sociology teaching in universities and colleges from the 1860's, witn some reference to instruction in social matters before this time. For the first years after its introduction attention is paid to each institution which offered sociology; for the later years particular institutions are singled out for special comment where noteworthy new departures were made. Chapter IV describes the regional development of sociology teaching from its beginnings in Eastern institutions. Graphic illustration of its spread is provided in a chronological series of maps. The second part of the chapter relates the development of sociology to contemporary movements in theology, particularly the ideas of Social Christianity and the Social Gospel. The extreme involvement of sociologists in these movements, and the encouragement given to sociology in certain denominations which were also prominent in the Social Gospel, are used as facts to support the contention that the outlooks upon society of sociologists and Social Gospel theologians were not only parallel but often so closely interwoven as to be inseparable. Chapter V goes into greater detail concerning the nature of the sociology being taught by describing various representative courses, with much illustrative material drawn from catalogue summaries of such courses. In the second part of the chapter some of the most popular textbooks for sociology courses are described. Chapter VI is concerned with those who taught sociology; four cases of opposition on the part of university authorities to certain aspects of the teaching of sociology are discussed. The education of sociology teachers is outlined with special reference to the influence which German higher education exercised over many of the most prominent American sociologists. Chapter VII documents the rise of sociology as a subject for graduate study in American universities and colleges, and includes lists of doctorates submitted in sociology and in sociological topics up to 1900. The subsequent careers of graduate students in sociology are briefly summarized. In the concluding chapter emphasis is placed upon the essentially American nature of sociology in the United States, its peculiar importance lying in its early and generally enthusiastic inclusion in the curricula of institutions of higher learning. Some contrasts are made in this respect with its position in Europe in the same period. Its popularity as a university subject is contrasted with the ill-developed nature of sociological theory in America at the time; some attempt is made to characterize such theory. A series of appendices is included to provide full documentation of the colleges and universities under review, a complete catalogue of courses in sociology, a bibliography of textbooks recommended in course descriptions together with writers cited without reference to particular works in such descriptions, chronological lists of the founding of departments of sociology and social science, a list of appointments in sociology and social science, and a catalogue of teachers of courses in sociology, outlining the institutions at which they taught, up to 1901.